CORRELATION BETWEEN REPORTED LEVELS OF THERAPEUTIC COMPLIANCE AND GEOGRAPHIC LOCATION OF PATIENT RESIDENCE - MIR, SHAKEEL AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Globally, healthcare suffers from the urban-rural and rich-poor divide. Our objective is to assess differences in therapeutic compliance between rural and urban adults. Methods: In a questionnaire-based study of outpatients, we assessed 400 adult outpatients selected by simple randomization. Results: The patients belonging to urban areas had better therapeutic compliance as compared to those belonging to rural areas. About 53.1% of patients from urban areas had good compliance as compared to 22.9% of patients from rural areas (p<0.001). Conclusion: Our findings reveal statistically significant differences in therapeutic compliance between rural and urban population.